Narrowing maize yield gaps in the rainfed plateau region of Odisha - Peramaiyan, Panneerselvam; McDonald, Andrew J.; Kumar, Virender; Craufurd, Peter; Wasim, Iftikar; Parida, Nabakishore; Pattnaik, Sanghamitra; Singh, Balwinder; Yadav, Ashok; Ajay, Anurag; Singh, Sudhanshu; Malik, Ram K. (Cambridge University Press, 2022)
Maize is the primary staple crop cultivated during the monsoon season in eastern India. However, yield gaps are large because of multiple factors, including low adoption rates of good agronomic management practices. This study aimed to narrow the maize yield gap using diverse agronomic and varietal interventions through field experiments over 2 years (2013–2014) in the rainfed plateau region of Odisha. As a result, maize yield increased by 0.9, 0.74, and 0.17 Mg ha−1under optimum plant population, fertilizer management, and herbicide-based weed management, respectively, over farmers’ current practices (Check). Moreover, when all three interventions were combined (‘best’ management practice), grain yields increased by 1.7 Mg ha−1in conservation tillage and 2.2 Mg ha−1in conventional tillage. We also observed that the combination of long-duration hybrids and best management practices (BMPs) increased grain yield by 4.0 Mg ha−1and profitability by $888 ha−1over farmers’ current practices. In addition, Nutrient Expert decision support tool-based fertilizer management along with BMPs increased grain yield by 1.7 Mg ha−1and profitability by $314 ha−1over farmers’ fertilizer practices (Check). These results suggest that the combination of maize hybrids and BMPs can improve the productivity and profitability of rainfed maize in the plateau region of Odisha. However, these entry points for intensification need to be placed in the context of varying investment requirements, input and output market conditions, and matched with farmer preferences and risk.